High‐Performance Photodetector based on a 3D Dirac Semimetal Cd3As2/Tungsten Disulfide (WS2) van der Waals Heterojunction. Issue 6 (2nd May 2021) - Zhang, Xingchao; Pan, Rui; Yang, Yunkun; Han, Qi; Liu, Xianchao; Zhang, Chaoyi; Zhou, Hongxi; Han, Jiayue; Gou, Jun; Wang, Jun
Abstract : Recently, heterojunction photodetectors have attracted significant interest due to the multiple degrees of freedom reorganization, integrating advantages of different typed materials. Herein, a high‐performance photodetector based on a 3D Dirac semimetal Cd3 As2 /tungsten disulfide (WS2 ) heterojunction is demonstrated, which is constructed by directly transferring exfoliated 2D few layer WS2 on Cd3 As2 nano‐belt and following by annealing treatment. The resulting Cd3 As2 /WS2 heterojunction device presents superior performance with a high on/off ratio (≈5.3 × 10 4 ) and a responsivity ( R i ) of about 223.5 AW −1 at 520 nm, as well as an outstanding detectivity ( D* ) of about 2.05 × 10 14 Jones at 808 nm near‐IR waveband. However, the optimized noise equivalent power (NEP) is evaluated about 6.17 × 10 −14  WHz −1/2 by the noise power density spectrum. The excellent performance can be attributed to a high‐quality heterostructure interface, strong light absorption capacity, and ultralow dark current in a Cd3 As2 /WS2 heterojunction system. This work provides a promising platform to develop a high‐performance optoelectronic device based on 3D Dirac semimetal and 2D TMDs families. Abstract : The high‐performance photodetector based on a 3D Dirac semimetal Cd3 As2 /tungsten disulfide (WS2 ) van der Waals heterojunction device is presented, in which the excellent performance including outstanding on/off ratio, R i, D*, and NEP can be attributed to a high‐quality heterostructure interface, strong light absorption capacity, and ultralow dark current in a Cd3 As2 /WS2 heterojunction system.